Expert-Led Module Improves Non-STEM Undergraduate Perception of and Willingness to Receive COVID-19 Vaccines - Morra, Christina N.; Adkins-Jablonsky, Sarah J.; Barnes, M. Elizabeth; Pirlo, Obadiah J.; Almehmi, Sloan E.; Convers, Bianca J.; Dang, Derek L.; Howell, Michael L.; Fleming, Ryleigh; Raut, Samiksha A. (Frontiers in Public Health, 2022)
As evidence mounted that existing prevention methods would be insufficient to end the COVID-19 pandemic, it became clear that vaccines would be critical to achieve and maintain reduced rates of infection. However, vaccine-hesitant sentiments have become widespread, particularly in populations with lower scientific literacy. The non-STEM major (called non-major) college students represent one such population who rely on one or more science classes to develop their scientific literacy and thus, become candidates of interest for the success of the COVID-19 vaccine campaign. As these students have fewer opportunities to learn how to identify reputable scientific sources or judge the validity of novel scientific findings, it is particularly important that these skills are included in the science courses offered to non-majors. Two concurrent non-major biology courses (N=98) at the University of Alabama at Birmingham in Spring 2021 completed Likert questionnaires with open-ended questions prior to and after an expert-led vaccine awareness educational intervention addressing vaccine-related concerns. In the module, experts gave presentations about COVID-19 related to microbiology, epidemiological factors, and personal experiences of COVID-19. Ten students agreed to participate in post-semester one-on-one interviews. Student interviews revealed that students perceived guest lecturers as providing more information and assurance. Questionnaire data showed an increase in student willingness to accept a COVID-19 vaccine as well as increased student perception of the COVID-19 vaccines as both safe and effective (Wilcoxon Rank Sum Test, p<0.05). However, the questionnaire data revealed 10 of 98 students remained vaccine-resistant, and these students expressed insufficient research and side effects as leading vaccination concerns. Overall, we show expert-led modules can be effective in increasing non-majors willingness to accept COVID-19 vaccines. We suggest more research explore the experiences of non-majors and guest lecturers, particularly as they relate to vaccination and vaccine concerns.